Tinjauan Perspektif Intelegensia Muslim terhadap Genealogi Kelas Menengah Muslim di Indonesia - Jati, Wasisto Raharjo (Program Pascasarjana UIN Sunan Ampel Surabaya, 2014)
This article aims to analyze genealogies of Muslim middle class in Indonesia. It can be traced from three primary sources such as bourgeoisies, pilgrimage trip (hajj) to Mecca and Medina, and education. These three sources have intertwined each other to build up Muslim middle class in social strata system that branch off in two model; bourguoises class and intellectual class. In this section, bourguoises tends to form trade alliance against Chinese domaniance and western traders who had been given privilieges from colonial regime. Meanwhile, intellectual class had focused to form ideal state for umat in Indonesia. Both classes are united altogether to form Islamic state as ultimate goals. High tension of political constellation in post colonial period had resulted in nationalist group as regulator class in Indonesia. Regarding political negotiation from nationalist, Indonesian Muslim middle class focused to establish Muslim society according to Medinan principles. Modern influence based on western style has affected Islamic values in grass roots level, and this resulted in the rise of modern Muslim society that embraced western style of life.